Lifestyle and dietary habits according to extent and purpose of Brazilian pregnant women: Vigitel epidemiological survey - Lima de Oliveira, João Paulo; Fróis, Laudicéia Ferreira; Avelar, Bruna Aparecida; Silva, Iasmim Fernanda Bernardo; Moura, Lahis Cristina Morais de; Teixeira, Lílian Gonçalves (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2024)
During pregnancy, food consumption is of utmost importance for the health of both the mother and the baby. A diet based on fresh and minimally processed foods, as opposed to ultra-processed foods, is essential to ensure health during pregnancy and postpartum. The objective of this study was to analyze the relationship between lifestyle habits and food consumption among pregnant Brazilian women. This is a cross-sectional study using data from pregnant women included in the Chronic Disease Risk Factor Surveillance System via Telephone Survey (Vigitel) in 2021. Food consumption, considered the outcome variable, was assessed through a food frequency questionnaire, focusing on consumption from the previous day. The NOVA classification was used to categorize foods as fresh or ultra-processed. The Shapiro-Wilk test was conducted to verify normality, and the Pearson Chi-square test was applied. A significance level of p < 0.05 was adopted. The sample consisted of 90 pregnant women. The analysis revealed a greater association with the consumption of ultra-processed foods among younger pregnant women compared to older age groups (p=0.020), as well as lower consumption of fresh foods (p=0.044). In conclusion, differences in food consumption were evident among pregnant women of different age groups. However, in order to understand the dietary patterns of pregnant women by regions of Brazil, it is necessary to conduct further studies to support programs aimed at the gestational period, reducing adverse effects and promoting maternal and child health.